AD, Volume 15, n° 1, 1990 - Full Issue - journal system (Africa Development, 1990)
Contents Notes on Transnationalisation Samir Amin ......................... 5 The Changing Land Use and Allocation Patterns of a West African Community George J.S. Dei ..................... 25 South Africa versus Southern African Development Coordination Conference Mohabe Nyirabu ..................... 45 Le Management africain: Mythe ou Réalité ? A. Lamine Dia ....................... 61 Quelle Stratégie de Développement pour l'Afrique Sub-Saharienne ? Hervé Diata ......................... 79 Book Reviews The History and Structure of African Poverty Tayambe Zeleza ...................... 97 The Political Economy of Crisis and Underdevelopment in Africa A. D. Adeoye ........................ 105 Publications Received ......................... 107 Index to Africa Development, Vol XIV, No 1 - 4, 1989